New-Onset Atrial Fibrillation in Patients With Primary Aldosteronism Receiving Different Treatment Strategies: Systematic Review and Pooled Analysis of Three Studies - Tsai, Cheng-Hsuan; Chen, Ya-Li; Pan, Chien-Ting; Lin, Yen-Tin; Lee, Po-Chin; Chiu, Yu-Wei; Liao, Che-Wei; Chen, Zheng-Wei; Chang, Chin-Chen; Chang, Yi-Yao; Hung, Chi-Sheng; Lin, Yen-Hung (Frontiers in Endocrinology, 2021)
Background: Primary aldosteronism (PA) is a common cause of secondary hypertension and associated with higher incidence of new-onset atrial fibrillation (NOAF). However, the effects of surgical or medical therapies on preventing NOAF in PA patents remain unclear. The aim of this meta-analysis study was to assess the risk of NOAF among PA patients receiving mineralocorticoid receptor antagonist (MRA) treatment, PA patients receiving adrenalectomy, and patients with essential hypertension (EH). Methods: We performed the meta-analysis of the randomized or observational studies that investigated the incidence rate of NOAF in PA patients receiving MRA treatment versus PA patients receiving adrenalectomy from database inception until December 01, 2020 which were identified from PubMed, Embase, and Cochrane Library. Results: A total of 172 related studies were reviewed, of which 3 fulfilled the inclusion criteria, including a total of 2,705 PA patients. The results of meta-analysis demonstrated a higher incidence of NOAF among the PA patients receiving MRA treatment compared to the PA patients receiving adrenalectomy (pooled odds ratio [OR]: 2.83, 95% confidence interval [CI]: 1.76-4.57 in the random effects model, I2 = 0%). The pooled OR for the PA patients receiving MRA treatment compared to the patients with EH was 1.91 (95% CI: 1.11-3.28). The pooled OR for the PA patients receiving adrenalectomy compared to the patients with EH was 0.70 (95% CI: 0.28-1.79). Conclusion: Compared to the EH patients and the PA patients receiving adrenalectomy, the patients with PA receiving MRA treatment had a higher risk of NOAF.